Slow light : invisibility, teleportation and other mysteries of light - Perkowitz, Sidney (Imperial College Press ; Distributed by World Scientific Pub., 2011)
Slow Light is a popular treatment of today's astonishing breakthroughs in the science of light. Even though we don't understand light's quantum mysteries, we can slow it to a stop and speed it up beyond its Einsteinian speed limit, 186,000 miles/sec; use it for quantum telecommunications; teleport it; manipulate it to create invisibility; and perhaps generate hydrogen fusion power with it. All this is lucidly presented for non-scientists who wonder about teleportation, Harry Potter invisibility cloaks, and other fantastic outcomes. Slow Light shows how the real science and the fantasy inspire.